Feedback regulation by trehalose 6‐phosphate slows down starch mobilization below the rate that would exhaust starch reserves at dawn in Arabidopsis leaves. (13th August 2018) - dos Anjos, Letícia; Pandey, Prashant Kumar; Moraes, Thiago Alexander; Feil, Regina; Lunn, John E.; Stitt, Mark
Abstract: Trehalose 6‐phosphate (Tre6P), a sucrose signaling metabolite, inhibits transitory starch breakdown in Arabidopsis ( Arabidopsis thaliana ) leaves and potentially links starch turnover to leaf sucrose status and demand from sink organs (Plant Physiology, 163, 2013, 1142). To investigate this relationship further, we compared diel patterns of starch turnover in ethanol‐inducible Tre6P synthase (iTPS) lines, which have high Tre6P and low sucrose after induction, with those in sweet11;12 sucrose export mutants, which accumulate sucrose in their leaves and were predicted to have high Tre6P. Short‐term changes in irradiance were used to investigate whether the strength of inhibition by Tre6P depends on starch levels. sweet11;12 mutants had twofold higher levels of Tre6P and restricted starch mobilization. The relationship between Tre6P and starch mobilization was recapitulated in iTPS lines, pointing to a dominant role for Tre6P in feedback regulation of starch mobilization. Tre6P restricted mobilization across a wide range of conditions. However, there was no correlation between the level of Tre6P and the absolute rate of starch mobilization. Rather, Tre6P depressed the rate of mobilization below that required to exhaust starch at dawn, leading to incomplete use of starch. It is discussed how Tre6P interacts with the clock to set the rate of starch mobilization.